(untitled) (Indonesian Journal of Agrarian Law, 2026)
This study examines the implementation of the conversion of Building Use Rights (Hak Guna Bangunan/HGB) into Ownership Rights (Hak Milik/HM) in Semarang City by highlighting various administrative, legal, and institutional challenges encountered in practice. The research employs a socio-legal approach that combines normative analysis of statutory regulations with empirical data obtained through field observations, in-depth interviews with stakeholders at the Semarang City Land Office of the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) and notaries, as well as document analysis. The findings reveal that the primary obstacles in the conversion process include overlapping authority among government agencies, incomplete application documents, and land status disputes, particularly involving land associated with government assets or land under Management Rights (Hak Pengelolaan/HPL). In addition, inadequate inter-agency coordination and the lack of integration within the land administration system further contribute to procedural delays and legal uncertainty for the public. These findings underscore the importance of strategic measures, including regulatory harmonization between central and local governments, institutional synchronization in land administration, and the digitalization of land registration services to enhance efficiency, transparency, and accountability in public service delivery. Therefore, this study contributes to the discourse on urban land governance by identifying practical obstacles in the field and offering policy recommendations aimed at strengthening legal certainty and the protection of land rights in urban areas of Indonesia.